A Pregnant Woman with Spina Bifida: Need for a Multidisciplinary Labor Plan - O’Neal, Mary Angela (Frontiers in Medicine, 2017)
Women with spina bifida present both obstetrical and anesthesia challenges. They are more likely to require a caesarian delivery and traditionally neuraxial anesthesia has been avoided due to concerns of worsening neurologic disability. The case of a pregnant woman with a history of a surgically corrected lipomeningocele and tethered cord is presented to illustrate the need for a comprehensive labor plan